Work Engagement as Mediator in Improving Organizational Performance in Marine Supplies Company - Yuswardi, Yuswardi; Sentoso, Antony; Wang, Devlin (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
Employee engagement and performance are critical drivers of organizational success, yet many firms still rely heavily on extrinsic motivators such as compensation. This study investigates the effects of leadership, compensation, human resource management (HRM) practices, knowledge sharing, and organizational culture on organizational performance, with work engagement as a mediating variable. The research was conducted among 386 employees working in marine supply companies in Batam, Indonesia, using purposive sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The analysis included convergent validity, reliability, and mediation testing through a bootstrapping procedure of 5,000 subsamples. Results indicate that leadership, HRM practices, knowledge sharing, and organizational culture have significant positive effects on work engagement and organizational performance, while compensation shows no significant influence. The findings support Herzberg’s Motivation-Hygiene Theory and Social Exchange Theory, emphasizing that intrinsic motivators and positive workplace relationships play a more substantial role in enhancing engagement and performance than financial rewards. The study offers both theoretical and practical implications for improving employee engagement and fostering sustainable organizational growth.